If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10 = 2x + 3x + -10 Reorder the terms: -10 = -10 + 2x + 3x Combine like terms: 2x + 3x = 5x -10 = -10 + 5x Add '10' to each side of the equation. -10 + 10 = -10 + 10 + 5x Combine like terms: -10 + 10 = 0 0 = -10 + 10 + 5x Combine like terms: -10 + 10 = 0 0 = 0 + 5x 0 = 5x Solving 0 = 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 0 + -5x = 5x + -5x Remove the zero: -5x = 5x + -5x Combine like terms: 5x + -5x = 0 -5x = 0 Divide each side by '-5'. x = 0 Simplifying x = 0
| h^2+1h-18=0 | | 42x*x=(50x*x)-20x | | 11.33=5+6.33m | | 11.3y=4.452 | | 18x+3x^2=45 | | 18=5x+9 | | 12.63=3.95+7m | | 12x+10-3x=-8 | | 82=5x+5x+2 | | 7x+4=5x+12 | | 27=n-38 | | x+20x+2x=-10-2x-15 | | 6x-21=33+9 | | 2.5x+15+0.5(x-4)=1.2x+2(0.9x-6) | | 1000=720+35h | | (4x^2+96x-1188)=0 | | 7x-1+4x=-1 | | 4a+25=75 | | 12x-28=-63 | | 12.3=0.41x | | 14x+9=7x+47 | | a^2+3x-ax-3a= | | 12(y-1)-4y=3(2y-2)+9y | | 13c+9-12c= | | 2(q+3)=4q+q-9 | | 5y= | | 12(y-1)-4y=3(y-2)+9y | | 7x-19=6x+53 | | -6x+2=-46 | | 6y-4x=4 | | 5+2x+x=3x-x+8 | | 15x^2-7x-4=0 |